2014
DOI: 10.5194/bgd-11-16085-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Technical note: Methionine, a precursor of methane in living plants

Abstract: Abstract. When terrestrial plants were identified as producers of the greenhouse gas methane, much discussion and debate ensued, not only about their contribution to the global methane budget, but also with regard to the validity of the observation itself. Although the phenomenon has now become more accepted for both living and dead plants, the mechanism of methane formation in living plants remains to be elucidated and its precursor compounds identified. We made use of stable isotope techniques to verify in v… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…By assuming UV radiation-induced CH 4 emissions from pectin as representing foliar CH 4 emissions, Bloom et al (2010) suggested a global contribution of 0.2e1.0 Tg plantderived CH 4 yr À1 . However, clear evidence shows that pectin is not the only precursor (Carmichael et al, 2014;Lenhart et al, 2014;Vigano et al, 2009), and several environmental stresses in addition to UV radiation have been observed to induce CH 4 production. Thus, whether Bloom et al (2010) underestimated the magnitude of this plant source of CH 4 has been a subject of debate (Bruhn et al, 2012;Fraser et al, 2015).…”
Section: Implications For the Global Ch 4 Budgetmentioning
confidence: 99%
See 4 more Smart Citations
“…By assuming UV radiation-induced CH 4 emissions from pectin as representing foliar CH 4 emissions, Bloom et al (2010) suggested a global contribution of 0.2e1.0 Tg plantderived CH 4 yr À1 . However, clear evidence shows that pectin is not the only precursor (Carmichael et al, 2014;Lenhart et al, 2014;Vigano et al, 2009), and several environmental stresses in addition to UV radiation have been observed to induce CH 4 production. Thus, whether Bloom et al (2010) underestimated the magnitude of this plant source of CH 4 has been a subject of debate (Bruhn et al, 2012;Fraser et al, 2015).…”
Section: Implications For the Global Ch 4 Budgetmentioning
confidence: 99%
“…In the second step, demethylation of the sulphoxide leads to methyl radical ( CH 3 ) formation via homolytic bond cleavage, and then to CH 4 (Table 1). This potential route of CH 4 production may exist in both plants and fungi because methionine has been identified as a common precursor of plant-and fungus-derived CH 4 (Lenhart et al, 2014. Accordingly, several stress factors (e.g.…”
Section: Fungimentioning
confidence: 99%
See 3 more Smart Citations